Modified antibacterial fabric and preparation method thereof

CN121272730BActive Publication Date: 2026-10-30GUANGZHOU BANGERHUA TEXTILE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511575012.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2026-10-30
Estimated Expiration
2045-10-31

AI Technical Summary

Technical Problem

抗菌持久性差:多数抗菌面料依赖表面喷涂抗菌剂(如季铵盐、纳米银),水洗10-15次后抗菌率显著下降(<80%),无法满足服装长期穿着需求;

Benefits of technology

(1)改性藻朊酸的服用性提升:藻朊酸与柔性聚合物(PVA/PEG)共混纺丝,柔性聚合物通过分子链缠绕改善藻朊酸的脆性,提升纤维断裂伸长率(15%-25%);同时,共混结构减少藻朊酸纤维水洗后的溶胀,强度损失率≤15%,满足服装耐水洗需求;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to alginic acid and its derivative technical field, specifically disclose a kind of modified antibacterial fabric and its preparation method, the modified antibacterial fabric includes by weight percentage: modified alginic acid fiber: 20%-40%;Auxiliary fiber: 51%-75%;Antibacterial microcapsule: 3%-8%;Functional additive: 0.5%-2%;Wherein, the modified alginic acid fiber is made by alginic acid and flexible polymer blend spinning;The antibacterial microcapsule is core-shell structure, with alginic acid derivative as shell, with natural antibacterial agent and sustained-release agent as core.The present application is through "alginic acid-flexible polymer blend modified fiber+natural essential oil β-cyclodextrin controlled-release microcapsule" design, solve the existing fabric pain point: modified fiber breaking strength 2.0-2.8 cN / dtex, wash 50 times loss ≤15%, improve wearability;Microcapsule makes fabric initial antibacterial rate ≥99%, wash 30 times retention rate ≥90%, and no irritation;Fabric strength ≥300N / m, air permeability ≥520mm / s, give consideration to comfort.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alginate and its derivatives, specifically to the application of alginate and its derivatives in antibacterial fabrics, and more specifically to a modified antibacterial fabric and its preparation method. Background Technology

[0002] As consumers increasingly demand functionality in clothing, antibacterial fabrics have become a market hotspot, but existing technologies suffer from the following key shortcomings: Poor antibacterial durability: Most antibacterial fabrics rely on surface spraying with antibacterial agents (such as quaternary ammonium salts and nano silver). After 10-15 washes, the antibacterial rate drops significantly (<80%), which cannot meet the needs of long-term clothing wear. Imbalance between skin-friendliness and functionality: To enhance the antibacterial effect, some antibacterial fabrics add high concentrations of inorganic antibacterial agents (such as unmodified nano silver), resulting in stiff fabrics (drape coefficient > 35%), reduced moisture absorption and breathability (breathability < 400mm / s), and poor wearing comfort. Application limitations of alginic acid: Alginic acid (alginic acid) and its derivatives (sodium alginate, calcium alginate) have natural skin-friendly and moisture-absorbing properties, but pure alginic acid fibers are brittle in the dry state, have poor water washing resistance (strength loss after washing >30%), and have weak antibacterial properties, making it difficult to use them directly as the core component of clothing fabrics. The modification process is complex: existing alginic acid modification methods mostly use chemical grafting (such as acrylic acid grafting), which requires high temperature and high pressure conditions, resulting in high process costs. Furthermore, residual chemical reagents may cause skin irritation, making them unsuitable for close-fitting clothing.

[0003] To address the aforementioned issues, there is an urgent need to design a clothing fabric with "modified alginate synergistic antibacterial properties." By optimizing the alginate modification method and antibacterial system, an integrated function of "long-lasting antibacterial effect, skin-friendly comfort, washability, and easy industrialization" can be achieved. Summary of the Invention

[0004] The purpose of this invention is to provide a modified antibacterial fabric and its preparation method to solve the problems mentioned in the background art.

[0005] To achieve the above objectives, the present invention provides a modified antibacterial fabric, comprising, by weight percentage: Modified alginate fiber: 20%-40%; auxiliary fiber: 51%-75%; antibacterial microcapsules: 3%-8%; functional additives: 0.5%-2%; The modified alginate fiber is made by blending alginate with a flexible polymer. The antibacterial microcapsules have a core-shell structure, with an alginate derivative as the shell and a natural antibacterial agent and a slow-release agent as the core. Through the blending of alginate and flexible polymer, the fiber breaking elongation is improved and the strength loss rate after 50 washes is reduced, achieving the first large-scale application of alginate in clothing fabrics. The antibacterial microcapsules use a natural antibacterial agent as the core material, avoiding skin irritation from chemical antibacterial agents and constructing a basic system of "long-lasting antibacterial + skin-friendly safety". The wall material uses sodium alginate-chitosan (homogeneous with modified alginate) to ensure the compatibility of microcapsules and fibers and avoid agglomeration that would cause the fabric to become stiff. The auxiliary fiber accounts for 51%-75%, which retains the skin-friendly and moisture-wicking properties of modified alginate while improving the fabric's durability (breaking strength ≥300N / m) through conventional fibers, making it suitable for high-frequency wearing scenarios such as underwear and sportswear.

[0006] Preferably, the flexible polymer is polyvinyl alcohol or polyethylene glycol, and the weight ratio of alginate to the flexible polymer is (70-90):(10-30).

[0007] Preferably, the antibacterial microcapsules have a particle size of 1-10 μm and a shell thickness of 0.5-2 μm; the weight ratio of the natural antibacterial agent to the sustained-release agent is (60-80):(20-40); the natural antibacterial agent is at least one of eucalyptus oil, tea tree oil, or eugenol; and the sustained-release agent is β-cyclodextrin. The particle size of 1-10 μm matches the fiber diameter (10-20 μm) to prevent microcapsule rupture during spinning and weaving (rupture rate <1%); the wall thickness of 0.5-2 μm balances controlled release and mechanical strength, allowing for slow penetration of the antibacterial agent while also withstanding finishing processes such as padding and baking. β-Cyclodextrin encapsulates natural antibacterial agents through hydrophobic cavities, slowing down the release rate. Combined with the secondary controlled release of the microcapsule wall material, this extends the release cycle of the antibacterial agent and significantly improves the antibacterial rate retention. Natural essential oil-based antibacterial agents (LD50 > 5000 mg / kg) are selected, which are non-allergenic. The natural aroma of essential oils can replace chemical fragrances, enhancing the wearing experience and making it suitable for clothing for infants, young children, and people with sensitive skin.

[0008] Preferably, the auxiliary fiber is at least one of cotton fiber, modal fiber, or polyester fiber. Combed cotton (fineness 1.2-1.5 dtex) is soft and skin-friendly, suitable for underwear; modal (1.0-1.2 dtex) is moisture-wicking and breathable, suitable for sportswear; hydrophilic polyester (1.5-2.0 dtex) is aging-resistant and dimensionally stable, suitable for outdoor clothing, meeting the differentiated needs of different clothing scenarios. Combed cotton / modal improves the softness of the fabric (drape coefficient ≤30%), and hydrophilic polyester improves the shrinkage of the fabric after washing (dimensional change rate ≤2%). Together with modified alginate fiber, it avoids the problem of "functional fibers causing fabric stiffness". The auxiliary fibers are all conventional raw materials in the clothing industry, with low procurement costs and mature supply chains. Their mixed use with modified alginate fiber can control the fabric cost to within 1.2 times that of conventional antibacterial fabrics while ensuring functionality, facilitating large-scale promotion.

[0009] Preferably, the functional additives include antioxidants and softeners in a weight ratio of (1-3):(7-9).

[0010] Preferably, the antioxidant is vitamin E or tea polyphenols; the softener is an organosilicon softener; and the modified antibacterial fabric has a unit area mass of 120-200 g / m². 2 Oxidizing agents (vitamin E / tea polyphenols) can inhibit the oxidation and aging of natural antibacterial agents and fibers, so that the antibacterial rate of the fabric decreases by ≤5% after 6 months of storage; silicone softeners can reduce the coefficient of friction between fibers, so that the fabric hand feel is improved from "slightly stiff" (hand feel level 3) to "soft" (hand feel level 4), and the drape coefficient is ≤30%, which meets the requirement of "close-fitting but not tight" clothing.

[0011] On the other hand, this invention discloses a method for preparing a modified antibacterial fabric, comprising the following steps: Alginic acid and a flexible polymer were dissolved in deionized water to prepare a spinning solution. The solution was then wet-spun, coagulated, stretched, and dried to obtain modified alginate fibers. Natural antibacterial agents were mixed with β-cyclodextrin to form the core, and sodium alginate and chitosan were dissolved in water to form the shell solution. After emulsification, dropwise addition of a coagulant, and cross-linking and solidification, antibacterial microcapsules were obtained. Modified alginate fiber and auxiliary fiber are mixed in proportion and then carded, spun, woven or knitted to form a base fabric; antibacterial microcapsules are mixed with functional additives to prepare a finishing solution, which is then used to impregnate and finish the base fabric. After pre-drying and baking, the modified antibacterial fabric is obtained.

[0012] Preferably, the concentration of the spinning solution is 6%-10%, and the viscosity is 3000-5000 cP; the coagulation bath for wet spinning is a calcium chloride solution with a concentration of 3%-5%, a coagulation temperature of 30℃-40℃, and a coagulation time of 5-10s; the stretching ratio is 1.5-2.5 times, the drying temperature is 60℃-80℃, and the drying time is 2-4h.

[0013] Preferably, the emulsification speed is 8000-12000 rpm and the emulsification time is 10-20 min; the coagulant is calcium chloride solution with a concentration of 2%-4%; the crosslinking and curing uses genipin or glutaraldehyde as crosslinking agent with a concentration of 0.1%-0.3%, a crosslinking temperature of 25℃-35℃, and a crosslinking time of 1-2 h.

[0014] Preferably, the padding liquid ratio is 70%-90%; the pre-drying temperature is 80℃-100℃, and the pre-drying time is 5-10 min; the baking temperature is 110℃-130℃, and the baking time is 3-5 min; in the weaving or knitting process, the warp and weft density of the woven fabric is (200-300) loops / 10cm × (180-280) loops / 10cm, and the loop density of the knitted fabric is (80-120) loops / 10cm. If a knitting process is used, antibacterial microcapsules are mixed into the mixed yarn of modified alginate fiber and auxiliary fiber in proportion during the spinning stage, and the dispersion uniformity of the microcapsules in the yarn is ≥90%; the concentration of antibacterial microcapsules in the finishing solution is 5%-10% (w / v), and the concentration of functional auxiliaries is 0.5%-1.5% (w / v).

[0015] The beneficial effects of this invention are as follows: (1) Improved wearability of modified alginate: Alginate is blended with flexible polymer (PVA / PEG) for spinning. The flexible polymer improves the brittleness of alginate through molecular chain entanglement, and increases the fiber breaking elongation (15%-25%). At the same time, the blended structure reduces the swelling of alginate fiber after washing, and the strength loss rate is ≤15%, which meets the requirements of garment washing resistance. (2) Long-lasting antibacterial synergy: The antibacterial microcapsules use sodium alginate-chitosan as the wall material (compatible with modified alginate components). The β-cyclodextrin in the core material slowly releases natural antibacterial agents through inclusion, which, combined with the controlled release effect of the microcapsule wall material, achieves "slow release-long-lasting antibacterial". The hydrophilicity of the modified alginate fiber can promote the migration of antibacterial agents to the fabric surface and improve antibacterial efficiency. (3) Skin-friendly and functional balance: auxiliary fibers (cotton / modal) enhance the softness of the fabric, and the silicone softener in the functional additives further optimizes the feel (drape coefficient ≤30%); the moisture absorption properties of modified alginic acid work synergistically with the breathable structure of the auxiliary fibers to ensure that the fabric breathability is ≥500mm / s, avoiding stuffiness when wearing. Detailed Implementation

[0016] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.

[0017] It should be noted that all reagents and raw materials used in this invention are commercially available, and the reagents are of analytical grade.

[0018] Alginic acid (alginic acid) is sourced from Shanghai Boyao Biotechnology Co., Ltd., and its model number is T0051; Sodium alginate is sourced from Qingdao Mingyue Seaweed Group Co., Ltd., with the model number MWF and a viscosity of 600-800 cps. Polyvinyl alcohol (PVA) is sourced from Sinopharm Chemical Reagent Co., Ltd., product number C183120010; The polyethylene glycol (PEG) is sourced from Sinopharm Chemical Reagent Co., Ltd., with product number XW012532268397; β-Cyclodextrin is sourced from Shanghai Yuanye Biotechnology Co., Ltd., with product number S11010; Chitosan is sourced from Zhejiang Jinke Pharmaceutical Co., Ltd., CAS No. 9012-76-4, with a degree of deacetylation ≥90%. The modified amino silicone oil is sourced from Zhejiang Hanbang New Material Co., Ltd., and its model number is TM100.

[0019] Example 1 Fabric composition (by weight %): Modified alginate fiber (alginic acid:PVA = 80:20 (weight ratio)): 30%; Auxiliary fiber (combed cotton 47wt% + hydrophilic polyester 18wt%): 65%; Antibacterial microcapsules (wall material: sodium alginate: chitosan 6:4 (weight ratio), core material: eucalyptus oil: β-cyclodextrin = 70:30 (weight ratio), shell material: core material = 1:5 (weight ratio)): 4.5%; Functional additives (tea polyphenols: modified amino silicone oil = 1:9 (weight ratio)): 0.5%; Unit area mass: 160g / m².

[0020] Preparation method: (1) Preparation of modified alginate fiber: Alginate and PVA were dissolved in deionized water to prepare a spinning solution with a total concentration of 8% (w / v, g / mL) and a viscosity of 4000 cP. The solution was then wet-spun, coagulated, stretched, and dried to obtain modified alginate fiber. The coagulation bath for wet spinning was a 4% (w / v, g / mL) calcium chloride solution, the coagulation temperature was 35℃, and the coagulation time was 8s. The stretching ratio was 2 times, the drying temperature was 70℃, and the drying time was 3h. (2) Preparation of antibacterial microcapsules: Eucalyptus oil and β-cyclodextrin were mixed as core material, and sodium alginate and chitosan were dissolved in deionized water to prepare a wall material solution with a total concentration of 2% (w / v, g / mL). The core material and wall material solution were mixed to obtain a microcapsule suspension. The microcapsule suspension was emulsified at 10000 rpm for 15 min, and 12 times the volume of spinning solution of 3% (w / v, g / mL) calcium chloride solution was added dropwise. Genipin was used as a crosslinking agent at 30℃ for 1.5 h to obtain antibacterial microcapsules. (3) Fabric forming: The modified alginate fiber is mixed with auxiliary fibers, and then combed, spun and woven (warp and weft density 250×230 threads / 10cm) to form a base fabric; antibacterial microcapsules, functional additives (tea polyphenols, modified amino silicone oil) and water are mixed to make a finishing solution with a solid content of 8%, and the base fabric is impregnated (80% of the liquid is rolled) and then pre-dried at 90℃ for 8min and baked at 120℃ for 4min to obtain the modified antibacterial fabric.

[0021] Example 2 Fabric composition (by weight %): Modified alginate fiber (alginic acid:PEG = 90:10 (weight ratio)): 20%; Auxiliary fiber (modal 70wt% + combed cotton 5wt%): 75%; Antibacterial microcapsules (wall material: sodium alginate: chitosan 7:3 (weight ratio), core material: tea tree oil: β-cyclodextrin = 60:40 (weight ratio), shell material: core material = 1:3 (weight ratio)): 3%; Functional additives (vitamin E: modified amino silicone oil = 1.5:8.5 (weight ratio)): 2%; Unit area mass: 120g / m².

[0022] Preparation method: (1) Preparation of modified alginate fiber: Alginate and PEG were dissolved in deionized water to prepare a spinning solution with a concentration of 6% (w / v, g / mL) and a viscosity of 3000 cP. The solution was then wet-spun, coagulated, stretched, and dried to obtain modified alginate fiber. The coagulation bath for wet spinning was a 3% (w / v, g / mL) calcium chloride solution, the coagulation temperature was 30℃, and the coagulation time was 5s. The stretching ratio was 1.5 times, the drying temperature was 60℃, and the drying time was 2h. (2) Preparation of antibacterial microcapsules: Tea tree oil and β-cyclodextrin were mixed as core material, and sodium alginate and chitosan were dissolved in deionized water to prepare a wall material solution with a concentration of 2.5% (w / v, g / mL). The core material and wall material solution were mixed to obtain a microcapsule suspension. The microcapsule suspension was emulsified at 8000 rpm for 10 min, and 10 times the volume of spinning solution of 2% (w / v, g / mL) calcium chloride solution was added dropwise. 0.1% (w / v, g / mL) glutaraldehyde was used as a crosslinking agent at 25℃ for 1 h to obtain antibacterial microcapsules. (3) Fabric forming: The modified alginate fiber is mixed with auxiliary fibers, and then combed, spun and knitted (80 loops / 10cm) to form a base fabric; antibacterial microcapsules, functional additives (vitamin E, modified amino silicone oil) and water are mixed to make a finishing solution with a solid content of 5%, and the base fabric is impregnated (70% of the solution is applied) and then pre-dried at 80℃ for 5min and baked at 110℃ for 3min to obtain the modified antibacterial fabric.

[0023] Example 3 Fabric composition (by weight %): Modified alginate fiber (alginic acid:PEG = 70:30 (weight ratio)): 40%; Auxiliary fiber (hydrophilic polyester 41wt% + combed cotton 10wt%): 51%; Antibacterial microcapsules (wall material: sodium alginate: chitosan 5:5 (weight ratio), core material: eugenol: β-cyclodextrin = 80:20 (weight ratio), shell material: core material = 1:8 (weight ratio)): 8%; Functional additives (tea polyphenols: modified amino silicone oil = 3:7 (weight ratio)): 1%; Unit area mass: 200g / m² 2 .

[0024] Preparation method: (1) Preparation of modified alginate fiber: Alginate and PEG were dissolved in deionized water to prepare a spinning solution with a concentration of 10% (w / v, g / mL) and a viscosity of 5000 cP. The solution was then wet-spun, coagulated, stretched, and dried to obtain modified alginate fiber. The coagulation bath for wet spinning was a 5% (w / v, g / mL) calcium chloride solution, the coagulation temperature was 40℃, and the coagulation time was 10s. The stretching ratio was 2.5 times, the drying temperature was 80℃, and the drying time was 4h. (2) Preparation of antibacterial microcapsules: Eugenol and β-cyclodextrin were mixed as core material, and sodium alginate and chitosan were dissolved in deionized water to prepare a wall material solution with a concentration of 3% (w / v, g / mL). The core material and wall material solution were mixed to obtain a microcapsule suspension. The microcapsule suspension was emulsified at 12000 rpm for 20 min, and 15 times the volume of spinning solution of 4% (w / v, g / mL) calcium chloride solution was added dropwise. Genipin was used as a crosslinking agent at 35℃ for 2 h to obtain antibacterial microcapsules. (3) Fabric forming: The modified alginate fiber is mixed with auxiliary fibers, and then combed, spun and woven (warp and weft density 300×280 threads / 10cm) to form a base fabric; antibacterial microcapsules, functional additives (tea polyphenols, modified amino silicone oil) and water are mixed to make a finishing solution with a solid content of 12%, and the base fabric is impregnated (90% of the liquid is rolled) and then pre-dried at 100℃ for 10min and baked at 130℃ for 5min to obtain the modified antibacterial fabric.

[0025] Example 4 Fabric composition (by weight %): Modified alginate fiber (alginic acid:PEG = 75:25 (weight ratio)): 35%; Auxiliary fiber (hydrophilic polyester 45wt% + combed cotton 13wt%): 58%; Antibacterial microcapsules (wall material: sodium alginate: chitosan 6:4 (weight ratio), core material: eugenol: β-cyclodextrin = 75:25 (weight ratio), shell material: core material = 1:6 (weight ratio)): 6%; Functional additives (vitamin E: modified amino silicone oil = 2:8 (weight ratio)): 1%; Unit area mass: 180g / m² 2 .

[0026] Preparation method: (1) Preparation of modified alginate fiber: Alginate and PEG were dissolved in deionized water to prepare a spinning solution with a concentration of 9% (w / v, g / mL) and a viscosity of 4500 cP. The solution was then wet-spun, coagulated, stretched, and dried to obtain modified alginate fiber. The coagulation bath for wet spinning was a 4.5% (w / v, g / mL) calcium chloride solution, the coagulation temperature was 38℃, and the coagulation time was 9s. The stretching ratio was 2.2 times, the drying temperature was 75℃, and the drying time was 3.5h. (2) Preparation of antibacterial microcapsules: Eugenol and β-cyclodextrin were mixed as core material, and sodium alginate and chitosan were dissolved in deionized water to prepare a wall material solution with a concentration of 2% (w / v, g / mL). The core material and wall material solution were mixed to obtain a microcapsule suspension. The microcapsule suspension was emulsified at 11000 rpm for 18 min, and 3.5% (w / v, g / mL) calcium chloride solution (13 times the volume of spinning solution) was added dropwise. Genipin (8 times the volume of suspension) was used as a crosslinking agent and crosslinked at 32℃ for 1.8 h to obtain antibacterial microcapsules. (3) Fabric forming: The modified alginate fiber is mixed with auxiliary fibers, and then combed, spun and knitted (100 loops / 10cm) to form a base fabric; antibacterial microcapsules, functional additives (vitamin E, modified amino silicone oil) and water are mixed to make a finishing solution with a solid content of 10%, and the base fabric is impregnated (85% of the solution is applied) and then pre-dried at 90℃ for 9min and baked at 125℃ for 4.5min to obtain the modified antibacterial fabric.

[0027] Comparative Example 1 30% of the modified alginate fiber was replaced with 30% alginate fiber (without PVA), and the rest was completely consistent with Example 1.

[0028] Comparative Example 2 The antibacterial microcapsules 4.5% were replaced with quaternary ammonium salt antibacterial agent cetyltrimethylammonium chloride 4.5% (using a surface spraying process (nozzle diameter 1mm, working pressure: 0.2MPa, spraying distance: 20cm, moving speed: 10m / min)), and the rest was completely consistent with Example 1.

[0029] Comparative Example 3 The antibacterial microcapsule core material (eucalyptus oil + β-cyclodextrin) was replaced with pure eucalyptus oil core material (without β-cyclodextrin), and the rest was completely consistent with Example 1.

[0030] Comparative Example 4 The antibacterial microcapsules are not used. The weight percentage of functional additives is increased to 5%, and the content of tea polyphenols in the functional additives is increased to 60%. The remaining components and process parameters are completely consistent with those in Example 1.

[0031] The modified antibacterial fabrics prepared in Examples 1-4 and Comparative Examples 1-4 were subjected to performance tests. The test standards and methods are as follows, and the test results are recorded in Table 1.

[0032] I. Fiber Mechanical Property Testing 1. Fiber breaking strength and elongation at break The test was conducted according to GB / T 14344-2008 "Test Method for Tensile Properties of Short Chemical Fibers". The specific steps were as follows: Modified alginate fiber samples were selected and cut into 20mm long short fiber segments. Ten valid samples were prepared in parallel. A fiber tensile testing machine was used, with the clamping distance set to 10mm and the tensile speed to 10mm / min. Both ends of the fiber were fixed to the machine clamps, and the machine was started to stretch the fiber until it broke. The maximum strength (unit: cN) and elongation at break (unit: mm) of each sample at break were recorded. Combined with the fiber linear density (unit: dtex), the breaking strength (unit: cN / dtex) was calculated according to "Breaking Strength = Breaking Strength / Linear Density". The elongation at break was calculated according to "Elongation at Break = (Elongation at Break / Initial Clamping Distance) × 100%". The average value of the 10 samples was taken as the test result.

[0033] 2. Fiber strength loss rate after 50 washes The pretreatment was performed according to the washing method in GB / T 3922-2013 "Textiles - Tests for Color Fastness to Perspiration", and the strength was tested in accordance with GB / T14344-2008. The specific steps were as follows: Prepare a sufficient amount of fiber samples and divide them into two groups: "before washing" and "after washing". The samples in the washing group were subjected to 50 cycles of washing under standard conditions - controlling the water temperature at 40±2℃, the detergent concentration at 0.5g / L, the liquor ratio at 1:50, and the washing time at 30min per wash. After washing, the samples were dried in an oven at 60±5℃ until constant weight. The breaking strength of the two groups of samples was tested separately. The loss rate was calculated as "strength loss rate = (average breaking strength before washing - average breaking strength after washing) / average breaking strength before washing × 100%", and the average value of three parallel tests was taken.

[0034] II. Fabric Mechanical Property Testing 1. Fabric breaking strength The test was conducted according to GB / T 3923.1-2013 "Textiles - Tensile Properties of Fabrics - Part 1: Determination of Breaking Strength and Elongation at Break (Strip Method)". The specific steps were as follows: Five warp and five weft samples were cut from the fabric, each sample measuring 250mm × 50mm, ensuring no burrs at the edges. Using a fabric tensile testing machine, the clamping distance was set to 200mm and the tensile speed to 100mm / min. The samples were fixed along their length in the clamps, and the machine was started to stretch until the samples broke. The maximum breaking strength (unit: N) of each sample was recorded. The results were converted to breaking strength per unit width (unit: N / m, i.e., breaking strength ÷ sample width 0.05m), and the average value of the five warp and five weft samples was taken as the final result.

[0035] 2. Fabric drape coefficient According to GB / T 23321-2009 "Determination of Drape of Textiles and Apparel", an umbrella-type drape apparatus was used for testing. The specific steps are as follows: cut a circular fabric sample with a diameter of 300 mm, ensuring that the sample is wrinkle-free; fix the center of the sample on the sample stage of the drape apparatus, allowing the sample to hang naturally in the dark box of the instrument; take a projected image of the sample after hanging using the instrument's built-in optical system, and the software automatically calculates the draped projected area of ​​the sample; calculate the result according to "drape coefficient = (draped projected area / original circular area of ​​sample) × 100%" (the smaller the coefficient, the better the drape of the fabric), perform 5 parallel tests, and take the average value as the final drape coefficient.

[0036] III. Antibacterial Performance Test The antibacterial rate of the fabric (against Staphylococcus aureus ATCC 29213 and Escherichia coli ATCC 25922) was tested according to GB / T20944.2-2007 "Evaluation of antimicrobial properties of textiles - Part 2: Absorption method". The specific steps were as follows: a 20mm × 20mm fabric sample was cut, sterilized at high temperature, and then laid flat in a sterile petri dish; 100μL of a 10% concentration of... 6 A bacterial suspension of CFU / mL was evenly dropped onto the sample surface and covered with a sterile polyethylene film to ensure full contact between the bacterial suspension and the sample. The petri dish was then placed in a constant temperature incubator at 37±1℃ and a relative humidity of 90% or higher and incubated for 24 hours. After incubation, 10 mL of sterile physiological saline was added, and the sample surface was thoroughly shaken to remove bacteria. The eluent was serially diluted, and the eluent of appropriate dilution was spread onto nutrient agar plates. After incubation for another 24 hours, the colony count was counted. A blank control group (bacterial suspension only, no fabric sample) was set up. The antibacterial rate was calculated as follows: "Antibacterial rate = (average colony count in the blank group - average colony count in the sample group) / average colony count in the blank group × 100%". If it is necessary to test the antibacterial rate after washing, the fabric must first be washed a specified number of times according to GB / T 3922-2013, dried, and then the above antibacterial test steps were repeated. The test was performed in parallel for 3 times and the average value was taken.

[0037] IV. Safety and Functional Testing Fabric air permeability: Tested using a fabric air permeability meter according to GB / T 5453-1997 "Determination of air permeability of textiles". The specific steps are as follows: Cut a 200mm×200mm fabric sample, ensuring that the sample is flat and undamaged; fix the sample on the test head of the air permeability meter, and set the test pressure difference to 100Pa (simulating the air pressure environment when the human body is wearing it); start the instrument and record the volume of air passing through the sample per unit time (unit: L / s); convert it to mm / s according to "air permeability = air volume ÷ (test area × time)" (1mm / s = 1L / (m²・s)), perform 5 parallel tests, and take the average value as the final air permeability. Table 1 Performance Test Results The core difference between Comparative Example 1 and Example 1 lies in the mechanical properties of the fibers and fabrics, while the antibacterial properties and breathability show no significant fluctuations. Data shows that the fiber breaking strength (1.4 cN / dtex) of Comparative Example 1 is only 63.6% of that of Example 1 (2.2 cN / dtex), the fiber breaking elongation (8.5%) is less than half that of Example 1 (18.2%), and the fiber strength loss rate after 50 washes (42.3%) is 3.5 times that of Example 1 (12.1%). This directly results in a fabric breaking strength (210 N / m) that is significantly lower than that of Example 1 (351 N / m), and a fabric drape coefficient (38.5%) that is significantly higher than that of Example 1 (26.2%). The root cause of this difference is that the hydrogen bonds between pure alginate fibers are dense, and the lack of chain segment entanglement of flexible polymer (PVA) results in brittle and hard fibers with poor washability, which in turn affects the durability and softness of the fabric. However, the antibacterial performance was not affected (initial antibacterial rate 99.1% / 98.7%) because the antibacterial microcapsule system was not changed. The fabric breathability (575mm / s) is close to that of Example 1 (587mm / s) because the fiber pore structure did not change significantly due to the lack of flexible polymer.

[0038] The only difference between Comparative Example 2 and Example 1 lies in the long-lasting antibacterial effect; the other indicators (fiber mechanics, fabric mechanics, and air permeability) are highly similar. Regarding the initial antibacterial rate, Comparative Example 2 (Staphylococcus aureus 98.3% / E. coli 97.8%) and Example 1 (Staphylococcus aureus 99.5% / E. coli 99.2%) showed little difference. However, after 30 washes, the antibacterial rate of Comparative Example 2 (Staphylococcus aureus 61.2% / E. coli 58.9%) was only 66%-68% of that of Example 1 (Staphylococcus aureus 92.5% / E. coli 91.8%). This is because the quaternary ammonium salt antibacterial agent adheres to the fabric surface through electrostatic adsorption, lacking the physical encapsulation and controlled release effect of antibacterial microcapsules, and is easily washed away during washing. The fiber mechanics, fabric mechanics, and air permeability are similar to Example 1 because the fiber composition (including flexible polymers), auxiliary fibers, and functional additives remained unchanged; only the type of antibacterial agent was adjusted, which did not affect other performance dimensions.

[0039] The key difference between Comparative Example 3 and Example 1 lies in the long-lasting antibacterial effect; other performance indicators (fiber mechanics, fabric mechanics, and air permeability) are almost identical. After 30 washes, the antibacterial rate of Comparative Example 3 (68.5% for Staphylococcus aureus and 66.1% for E. coli) was higher than that of Comparative Example 2, but still significantly lower than that of Example 1 (92.5% for Staphylococcus aureus and 91.8% for E. coli), with a difference of 24-26 percentage points. The core reason is the lack of the "encapsulation and controlled release" effect of β-cyclodextrin on eucalyptus oil—without β-cyclodextrin, the oil cannot be stably encapsulated and is easily released rapidly through the microcapsule wall material, and is more easily lost with the seepage during washing, resulting in a decrease in long-lasting antibacterial ability. The fiber mechanics, fabric mechanics, and air permeability are basically the same as those of Example 1 because the microcapsule wall material (sodium alginate-chitosan), fiber composition, and finishing process have not changed; only the core material composition has been adjusted, which has not affected the physical properties and breathability structure of the fabric.

[0040] The differences between Comparative Example 4 and Example 1 lie in the efficiency and longevity of antibacterial performance and the fabric feel, while other mechanical properties show minor differences. Regarding the initial antibacterial rate, Comparative Example 4 (88.5% Staphylococcus aureus / 86.3% E. coli) was significantly lower than Example 1 (99.5% Staphylococcus aureus / 99.2% E. coli), with a difference exceeding 10 percentage points. After 30 washes, the antibacterial rate of Comparative Example 4 (52.3% Staphylococcus aureus / 49.8% E. coli) was less than 57% of that of Example 1, while the fabric drape coefficient (32.0%) was higher than that of Example 1 (26.2%). This is because the antibacterial efficiency of tea polyphenols in the functional additives is inherently lower than that of natural essential oil microcapsules, and without the physical protection of microcapsules, tea polyphenols are easily lost during washing and oxidized during storage, leading to a significant decrease in antibacterial effect. Furthermore, the increased proportion of tea polyphenols (to 60%) to enhance the antibacterial effect made the fabric feel stiffer and increased the drape coefficient. The fiber mechanics, fabric breaking strength, and air permeability are similar to those of Example 1 because the fiber composition is unrelated to the microcapsules and was not affected by the adjustments.

[0041] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details of the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, and these simple modifications all fall within the protection scope of the present invention. Furthermore, it should be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe the various possible combinations.

[0042] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.

Claims

1. A modified antibacterial fabric, characterized in that, By weight percentage, it consists of the following components: Modified alginate fiber: 20%-40%; auxiliary fiber: 51%-75%; antibacterial microcapsules: 3%-8%; functional additives: 0.5%-5%; The modified alginate fiber is made by blending alginate with a flexible polymer and spinning; the antibacterial microcapsules have a core-shell structure, with an alginate derivative as the shell and a natural antibacterial agent and a sustained-release agent as the core; the particle size of the antibacterial microcapsules is 1-10 μm, and the shell thickness is 0.5-2 μm; the functional additives are antioxidants and softeners; the flexible polymer is polyvinyl alcohol or polyethylene glycol; the natural antibacterial agent is at least one of eucalyptus oil, tea tree oil, or eugenol; the sustained-release agent is β-cyclodextrin; and the auxiliary fiber is at least one of cotton fiber, modal fiber, or polyester fiber.

2. The modified antibacterial fabric according to claim 1, characterized in that, The weight ratio of the alginate to the flexible polymer is (70-90):(10-30).

3. The modified antibacterial fabric according to claim 1, characterized in that, The weight ratio of the natural antibacterial agent to the sustained-release agent is (60-80):(20-40).

4. The modified antibacterial fabric according to claim 1, characterized in that, The functional additives are antioxidants and softeners, with a weight ratio of (1-3):(7-9).

5. The modified antibacterial fabric according to claim 4, characterized in that, The antioxidant is vitamin E or tea polyphenols; the softener is an organosilicon softener; and the modified antibacterial fabric has a unit area mass of 120-200 g / m².

6. A method for preparing a modified antibacterial fabric according to any one of claims 1-5, characterized in that, Includes the following steps: Alginic acid and a flexible polymer were dissolved in deionized water to prepare a spinning solution. The solution was then wet-spun, coagulated, stretched, and dried to obtain modified alginate fibers. Natural antibacterial agents were mixed with β-cyclodextrin to form the core, and sodium alginate and chitosan were dissolved in water to form the shell solution. After emulsification, dropwise addition of a coagulant, and cross-linking and solidification, antibacterial microcapsules were obtained. Modified alginate fiber and auxiliary fiber are mixed in proportion and then carded, spun, woven or knitted to form a base fabric; antibacterial microcapsules are mixed with functional additives to prepare a finishing solution, which is then used to impregnate and finish the base fabric. After pre-drying and baking, the modified antibacterial fabric is obtained.

7. The method for preparing the modified antibacterial fabric according to claim 6, characterized in that, The spinning solution has a concentration of 6%-10% and a viscosity of 3000-5000 cP; the coagulation bath for wet spinning is a calcium chloride solution with a concentration of 3%-5%, a coagulation temperature of 30℃-40℃, and a coagulation time of 5-10s; the stretching ratio is 1.5-2.5 times, the drying temperature is 60℃-80℃, and the drying time is 2-4h.

8. The method for preparing the modified antibacterial fabric according to claim 6, characterized in that, The emulsification speed is 8000-12000 rpm, and the emulsification time is 10-20 min; the coagulant is calcium chloride solution with a concentration of 2%-4%; the crosslinking and curing uses genipin or glutaraldehyde as crosslinking agent with a concentration of 0.1%-0.3%, a crosslinking temperature of 25℃-35℃, and a crosslinking time of 1-2 h.

9. The method for preparing the modified antibacterial fabric according to claim 6, characterized in that, The padding liquid ratio is 70%-90%; the pre-drying temperature is 80℃-100℃, and the pre-drying time is 5-10min; the baking temperature is 110℃-130℃, and the baking time is 3-5min; in the weaving or knitting process, the warp and weft density of the woven fabric is (200-300) loops / 10cm × (180-280) loops / 10cm, and the loop density of the knitted fabric is (80-120) loops / 10cm.

Citation Information

Patent Citations

  • Method for preparing medical gauze having bacteriostatic effect

    CN108977977A

  • Plant essential oil microcapsule and preparation method thereof

    CN114177847A